Determinants of Household Food Security: The Case of Mareko Woreda, Ethiopia - Zerihun Nigussie; Ayalneh Bogale (Journal of Agricultural Extension Management, 2025)
Food insecurity has begun to make a serious impact and has become a prominent issue in the development debate recently. This study was undertaken in Ethiopia to identify the socio-economic determinants of food security. The data analyzed came mainly from a survey of 150 rural households in 5 different Kebeles of the Woreda, which were selected based on probability proportional to size. The household food security/ insecurity status was measured by the direct measurement of household food consumption in the 12 months study period using the household food balance sheet model as reported from household recall. Logistic regression model was applied to identify the correlates of household food security in the study area. Land holding, total cereal production, income obtained from safety-net, number of oxen owned, off-farm and non-farm income, sex of household head and livestock holding were found to affect household food security positively; while adult equivalent household size and quantity of chemical fertilizer applied were found to have negative effect. Based on the findings of the study, short term and long term interventions are recommended to alleviate the food insecurity problem.